2018
DOI: 10.1016/j.molbiopara.2018.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Purification of native Sigma class glutathione transferase from Fasciola hepatica

Abstract: Fascioliasis is a parasitic disease of grazing livestock and a threat to global food security by significantly reducing the production value of sheep, goats and cattle. Moreover, the zoonotic parasite is also a re-emerging food borne threat to human populations. Driven by climate change, the prevalence of fascioliasis is set to increase. Efforts to control the main causative agent, Fasciola hepatica, are hampered by short lived chemotherapy approaches that are becoming increasingly obsolete due to therapeutic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…During infestation, adult F. hepatica can release GST (as one of important components of ESPs), which is not only involved in the immune responses of the host, but related to the resistance of F. hepatica to triclabendazole, and also reduced liver disease. Therefore, GST is often used as a candidate vaccine or drug target for research [ 14 , 16 , 35 ]. Previous research has reported that the main component of ESPs of this parasite may suppress immune responses of the host by modulating the function of antigen presentation cells (APCs) [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…During infestation, adult F. hepatica can release GST (as one of important components of ESPs), which is not only involved in the immune responses of the host, but related to the resistance of F. hepatica to triclabendazole, and also reduced liver disease. Therefore, GST is often used as a candidate vaccine or drug target for research [ 14 , 16 , 35 ]. Previous research has reported that the main component of ESPs of this parasite may suppress immune responses of the host by modulating the function of antigen presentation cells (APCs) [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…All SDS-PAGE separations were conducted as described previously [ 63 ]. Successful rSmLEV1.3 purification was confirmed by SDS-PAGE separation, followed by Coomassie Blue staining [ 64 ] and anti-His 6 western blot analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The anti-SmTSP-2 antibody was a kind gift from Professor Alex Loukas (James Cook University, Australia). For western blotting, 1.5 μg of parasite extract or 100 ng of each EV fraction was mixed with 2x SDS non-reducing sample buffer (0.143 M SDS + 0.125 M Tris (pH 6.8) + 20% v/v glycerol) and incubated for 5 min at 100°C, prior to separation by 1D-SDS-PAGE and transfer to polyvinylidene difluoride (PVDF) membrane as described previously [ 63 ]. Membrane blocking occurred for 2 h at room temperature in blocking buffer (PBS containing 0.2% fish skin gelatine 0.3% Tween 20).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immediately prior to performing tandem mass spectrometry the dried peptides were re-suspended in 20 μL 0.1% v/v formic acid. For 2D SDS PAGE protein spots, the method of Duncan et al (2018) was utilized for LC-MSMS. For whole A. perfoliata Orbitrap Fusion™ Tribrid™ mass spectrometer (Thermo Scientific™), with EASY-Spray™ Source, coupled to an UltiMate™ 3000 RSLCnano System (Thermo Scientific™) as per methods of Rooney et al (2022).…”
Section: Trypsin Digestion and Mass Spectrometrymentioning
confidence: 99%